Tmc Reliance Is Biased by the Hair Cell Subtype and Position Within the Ear - Zhu, Shaoyuan; Chen, Zongwei; Wang, Haoming; McDermott, Brian M. (Frontiers in Cell and Developmental Biology, 2021)
Hair cells are heterogenous, enabling varied roles in sensory systems. An emerging hypothesis is that the transmembrane channel-like (Tmc) proteins of the hair cell’s mechanotransduction apparatus vary within and between organs to enable encoding of different mechanical stimuli. Five anatomical variables that may coincide with different Tmc use by a hair cell within the ear are the containing organ, cell morphology, cell position within an organ, axis of best sensitivity for the cell, and the hair bundle’s orientation within this axis. Here, we test this hypothesis in the organs of the zebrafish ear using a suite of genetic mutations. Transgenesis and quantitative measurements demonstrate two morphologically distinct hair cell types in the central thickness of the lateral crista: short and tall. In contrast to what has been observed, we find that tall hair cells predominantly depend on Tmc1. Short hair cells mainly rely on Tmc2 isoforms. However, tall and short hair cell Tmc dependencies are not absolute, and variations in Tmc components exist within these subtypes. We also mapped Tmc1 use in the saccule of mutant larvae that depend on just one Tmc protein, Tmc1, to hear and demonstrate that hair cells that use Tmc1 are found in the posterior region of the saccule, within a single axis of best sensitivity, but hair bundles with opposite orientations retain function. Overall, we have determined that Tmc reliance in the ear is dependent on the organ, subtype of hair cell, position within the ear, and axis of best sensitivity.